Exosome-like Nanoparticles from Ginger Rhizomes Inhibited NLRP3 Inflammasome Activation (P06-072-19). (13th June 2019) - Chen, Xingyi; Yu, Jiujiu
Abstract: Objectives: The NLRP3 inflammasome is a key regulator of innate immune responses, and its aberrant activation has been implicated in the pathogenesis of many complex diseases including multiple sclerosis, type 2 diabetes and atherosclerosis. Our study aimed to identify the food-borne exosome-like nanoparticles (ELNs) that inhibit NLRP3 inflammasome in macrophages. Methods: ELNs from nine vegetables or fruits were purified using ultracentrifugation, incubated with bone-marrow derived macrophages, followed by the activation of NLRP3 inflammasome. After the dietary ELNs with strong inhibitory effects on inflammasome were identified, their roles in the inflammasome assembly and downstream pathways were further examined. Results: We identified that ELNs from ginger rhizomes (G-ELNs) strongly inhibited NLRP3 inflammasome activation. We verified that G-ELNs were exosome-like nanoparticles containing biomolecules including RNAs, proteins, and lipids. The G-ELNs were taken up by macrophages. G-ELNs suppressed the downstream pathways of NLRP3 inflammasome activation including Casp1 auto-cleavage, interleukin (IL)-1 and IL-18 secretion, and pyroptotic cell death. G-ELNs blocked the assembling steps of NLRP3 inflammasome, but had no effects on protein levels of a key mediator of NLRP3 inflammasome NIMA-related kinase 7 (Nek7), or the inflammasome subunits NLRP3, ASC, and Casp1. Conclusions: Our findings identified G-ELNs as a new potent agent that blocks NLRP3 inflammasome assembly and activation. Funding Sources: This work was supported by the National Institutes of Health (NIH) 1P20GM104320 Nebraska Center Prevention of Obesity Diseases (NPOD) Seed Grant and Project Leader Grant, and the United States Department of Agriculture (USDA) National Institute of Food and Agriculture (NIFA) Hatch Project 1015948.